(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
Background: Different laser types have been used for the treatment of hypertrophied inferior nasal turbinates. The clinical experiences of its treatment by means of a diode laser are presented. Methods: A total of 45 patients suffering from nasal obstruction due to hypertrophied inferior turbinates (HIT) were treated with a continuous diode laser (14 W- 940 nm) in "contact" mode and under local anesthesia. Thirty patients (16 with allergic rhinitis and 14 with vasomotor rhinitis) were included into this clinical trial with a follow-up of 6 months. The study was conducted by a questionnaire, photo documentation, conventional radiology of the paranasal sinuses, and histology. Results: The mean operation time took 8 min/turbinate, no nasal packing was necessary and no immediate complications (e.g., bleeding) were observed. Statistical analysis revealed significant subjective improvement (86%) of the nasal airflow and nasal cavity volume (photo documentation) 6 months after laser surgery. In addition, complete relief of headache was achieved in 32%. The remission rates of persistent rhinorrhoea and post-nasal dripping were, at about 88% and 64%, respectively. Atrophic change and synechiae had not been observed. Conclusions: Diode laser treatment of HIT is a useful procedure, which can be performed as an outpatient surgery under local anesthesia, resulting in a controlled coagulation and ablation of the soft tissue. The short operation time and the good results provide an excellent patient acceptance. Key words: Diode Laser; Hypertrophied Inferior Turbinate; Turbinoplasty. DOI: 10.3329/bjo.v16i1.5778 Bangladesh J Otorhinolaryngol 2010; 16(1): 29-34